Sentimental biopower: rereading the Spanish nineteenth century. (3rd April 2021) - Labanyi, Jo
ABSTRACT: Drawing on the theorization by Luisa Passerini and Kyla Schuller of Eurocentric notions that linked racial superiority to emotional refinement, the article will trace a substratum of biopolitical thinking across a range of Spanish texts from the 1830s to the 1880s. The use of medieval settings in Romantic historical fiction will be related to the contemporaneous belief that courtly love was the basis of European civilization. I will then explore how the concept of "impressibility" as the basis of moral improvement, derived from Lamarckian evolutionary theory, underpins a variety of literary and reform writings. I argue that these texts, which place the female capacity for sentiment at their center, are the other side of a biopolitical construction of class and race hierarchies.